(3QMdI GHf RGchQs - (3eMeO Hf bGSe Hf eMeO Hf YHO GdhGMO GdaGSj, CHh YHO Gddg, GHf RGchQ , J (B1120 (3g` s
(3ChdgG (B:s
(3Ef CLed eG NHQJ Hg CfaGS GdGbdGe feGQb GdWQhS hHYO aEf GdQMdI efg ef Gddg s
(3BNQgG (B:s
(3hCHhM ai aYdge HeG djS LhGfMi bGd cGJHI LeYJ Gdjg ehGcH GdGMSGf bO GfJgi s
(3HBNQg ChQGb JMJhi Ydi GOYjI hCTYGQ hHgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B7s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3eJaQbGJs